El cabildo catedralicio de Évora en la Edad Moderna - Díaz, Antonio J. (2014)
Certainly, in the Early Modern Age, the wealthiest, prestigious and powerful Portuguese cathedral chapter was that of Evora. However, there is not a single study on this institution focused on modern centuries so far. Therefore, with this article we intend to achieve two objectives. On the one hand, we study the institutional evolution of the chapter, from the elevation of Evora to metropolitan see until the early 19th century. On the other hand, we analyse the access channels to the chapter in order to know the balance of powers between the Holy See and the archdiocese and the extraordinary channels (coadjutorships and resignations) used by certain groups to preserve and transmit the canonries and dignities of the chapter, almost turned into inherited assets.